Rosacea - new data on pathogenesis and treatment - Waldemar Placek; Hanna Wolska (Termedia Publishing House, 2016)
Rosacea is a common dermatosis more prevalent in females, significantly impairing quality of life. Currently erythematous, papulo-pustular and phymatous subtypes are distinguished, which do not necessarily represent consecutive stages. Recent findings indicate in the pathogenesis of rosacea the role of the impaired innate immune system and vascular abnormalities. Additionally, the role of genetic and infectious factors is suggested. The therapy of rosacea is directed not only against inflammatory changes but also anti-parasitic. In topical treatment the most commonly used are metronidazole and azelaic acid. Other drugs are topical antibiotics, antiparasitic agents such as ivermectin and preparations directly influencing erythema. In more severe cases tetracyclines or macrolides are used, and in the most severe cases, isotretinoine. As ultraviolet light is a recognized trigger for rosacea, regular sunscreen use is necessary. Also, proper diet is indicated. Presently in the treatment of rosacea more and more techniques using different lights are employed.